2012
DOI: 10.1111/j.1745-7599.2012.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity: Can electronic medical records customized with clinical practice guidelines improve screening and diagnosis?

Abstract: Customizing EMR with clinical practice guidelines improved adherence to recommendations for screening and identification of childhood overweight and obesity. Increased recognition and diagnosis will lead to improved interventions and improve outcomes for childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…BMI documentation increased from 64% to 86% (P < .001), BMI percentile documentation increased from 31% to 76% (P < .001), BP documentation improved from 83% to 97% (P < .001), and BP percentile documentation improved, increasing from 1% to 35% (P < .005). The significance of these findings is consistent with other studies 8,10 and supports the role of HIT in improving pediatric obesity recognition, documentation, and interventions.…”
Section: Background and Significancesupporting
confidence: 90%
See 1 more Smart Citation
“…BMI documentation increased from 64% to 86% (P < .001), BMI percentile documentation increased from 31% to 76% (P < .001), BP documentation improved from 83% to 97% (P < .001), and BP percentile documentation improved, increasing from 1% to 35% (P < .005). The significance of these findings is consistent with other studies 8,10 and supports the role of HIT in improving pediatric obesity recognition, documentation, and interventions.…”
Section: Background and Significancesupporting
confidence: 90%
“…10 The EHR was structured using current evidence-based practice guidelines 6,11 and provided tailored information to parents and children. After implementation, the authors found a significant increase in screenings; children were 62% more likely to have a BMI recorded with EHR growth chart, and questionnaire completion improved 94% with the EHR.…”
Section: Background and Significancementioning
confidence: 99%
“…13,[15][16][17][18] Structured documentation templates for capturing data have also been shown to improve overall data quality by producing nursing documentation that is more complete, relevant, and comprehensive. [19][20][21] Several studies have evaluated the effectiveness of computerized documentation templates, merged with disease-specific content, to help standardize clinician documentation. 18,[21][22][23][24] Thus, documentation of disease-specific content for stroke may improve with the use of evidence-based content.…”
Section: Introductionmentioning
confidence: 99%
“…The literature supports schools as vital to educating students on how to eat appropriately and choose the best meal [5] it is important that children are educated about healthy choices to reduce their risk of obesity-related diseases. The purpose of this project is to provide an educational program specific to healthy food choices to elementary school teachers for implementation in the classroom.…”
Section: Implementing An Education Program On Healthy Food Choices Inmentioning
confidence: 99%
“…Obesity is related to more general practitioner visits, more school absences, more health-related limitations and overall lower general health scores [4]. some of the more prevalent chronic diseases associated with obesity include: Increased blood pressure, increased cholesterol, heart disease and diabetes [5].…”
Section: Implementing An Education Program On Healthy Food Choices Inmentioning
confidence: 99%